Understanding and History of the Development of Islamic Boarding Schools in Indonesia - Arief Firmansyah; Amirudin (Penerbit Hellow Pustaka, 2023)
Pesantren is the oldest educational institution with unique Indonesian characteristics, so that various perspectives have been studied, especially the periodization of its history. However, the study of the periodization of the history of pesantren so far has tended to be general in terms of their roles and work. Not to mention the simplicity, the manhaj system that seems to be what it is, the relationship between kyai and santri and the physical situation is simple. On this basis, this paper will examine more deeply about the role of Islamic boarding schools in the history of education in Indonesia. Based on historical-periodic analysis Through literature study, the history of Islamic boarding schools in Indonesia is divided into five periods, namely: birth and development, evolution, ideological bastion, and Muslim development media. Meanwhile, his role is as an inspiration in formulating the national education system, creating educational intellectua figures and character education models.